Critical periods after stroke study: translating animal stroke recovery experiments into a clinical trial - Dromerick, Alexander W.; Edwardson, Matthew A.; Edwards, Dorothy F.; Giannetti, Margot L.; Barth, Jessica; Brady, Kathaleen P.; Chan, Evan; Tan, Ming T.; Tamboli, Irfan; Chia, Ruth; Orquiza, Michael; Padilla, Robert M.; et al. (Frontiers in Human Neuroscience, 2015)
Introduction: 795,000 Americans will have a stroke this year, and half will have a chronic hemiparesis. Substantial animal literature suggests that the mammalian brain has much potential to recover from acute injury using mechanisms of neuroplasticity, and that these mechanisms can be accessed using training paradigms and neurotransmitter manipulation. However, most of these findings have not been tested or confirmed in the rehabilitation setting, in large part because of the challenges in translating a conceptually straightforward laboratory experiment into a meaningful and rigorous clinical trial in humans. Through presentation of methods for a Phase II trial, we discuss these issues and describe our approach. Methods: In rodents there is compelling evidence for timing effects in rehabilitation; motor training delivered at certain times after stroke may be more effective than the same training delivered earlier or later, suggesting that there is a critical or sensitive period for strongest rehabilitation training effects. If analogous critical/sensitive periods can be identified after human stroke, then existing clinical resources can be better utilized to promote recovery. The Critical Periods after Stroke Study (CPASS) is a phase II randomized, controlled trial designed to explore whether such a sensitive period exists. We will randomize 64 persons to receive an additional 20 hours of upper extremity therapy either immediately upon rehab admission, 2-3 months after stroke onset, 6 months after onset, or to an observation-only control group. The primary outcome measure will be the Action Research Arm Test at one year. Blood will be drawn at up to 3 time points for later biomarker studies. Conclusion: CPASS is an example of the translation of rodent motor recovery experiments into the clinical setting; data obtained from this single site randomized controlled trial will be used to finalize the design of a Phase III trial.